Ice Nucleation Induced by Pseudomonas syringae - Maki, Leroy R. (1974)
Broth cultures of suspensions of Pseudomonas syringae isolated from decaying alder leaves (Alnus tenuifolia) were found to freeze at very warm (-1.8 to -3.8 C) temperatures. The initiation of freezing appears associated with the intact cell and not with extracellular material. Chemical treatments and physical destruction of the cell destroy activity. Bacteria must be in concentrations of approximately 10(6)/ml before freezing at warm temperatures occurs.